No more hypoglycaemia on days with physical activity and unrestricted diet when using a closed‐loop system for 12 weeks: A post hoc secondary analysis of the multicentre, randomized controlled Diabeloop WP7 trial. Issue 9 (3rd June 2021) - Franc, Sylvia; Benhamou, Pierre‐Yves; Borot, Sophie; Chaillous, Lucy; Delemer, Brigitte; Doron, Maeva; Guerci, Bruno; Hanaire, Hélène; Huneker, Erik; Jeandidier, Nathalie; Amadou, Coralie; Renard, Eric; et al.
Abstract: A post hoc analysis of the Diabeloop WP7 multicentre, randomized controlled trial was performed to investigate the efficacy of the Diabeloop Generation‐1 (DBLG1) closed‐loop system in controlling the hypoglycaemia induced by physical activity (PA) in real‐life conditions. Glycaemic outcomes were compared between days with and without PA in 56 patients with type 1 diabetes (T1D) using DBLG1 for 12 weeks. After the patient announces a PA, DBLG1 reduces insulin delivery and, if necessary, calculates the amount of preventive carbohydrates (CHO). Daily time spent in the interstitial glucose range less than 70 mg/dL was not significantly different between days with and without PA (2.0% ± 1.5% vs. 2.2% ± 1.1%), regardless of the intensity or duration of the PA. Preventive CHO intake recommended by the system was significantly higher in days with PA (41.1 ± 35.5 vs. 21.8 ± 28.5 g/day; P  < .0001), and insulin delivery was significantly lower (31.5 ± 10.5 vs. 34.0 ± 10.5 U/day; P  < .0001). The time spent in hyperglycaemia and the glycaemic variation coefficient increased significantly on days with PA. In real‐life conditions, the use of DBLG1 avoids PA‐induced hypoglycaemia. Insulin adjustments and preventive CHO recommendation may explain this therapeutic benefit.